Mikroanatomi Hepar Tikus Putih Setelah Pemberian Berbagai Kadar Vco dan Olive Oil - Yuniwarti, Enny Yusuf Wachidah; Djaelani, Muhammad Anwar (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2016)
This research aimed to determine differences in Â hepatocyte cells after feeding saturated fatty acid and unsaturated fatty acid. Elevated level of fatty acid may contribute to damage of celluar hepatocytes. This research used 25 white rat. The method applied was Completely Randomized Design in which the factor was five levels of VCO and Olive Oil namely P1, P2, P3, P4 and P5. P1was the control group, P2 was a group with 10 mL Olive Oil /kg feed. P3 was a group with 5 mL Olive Oil /kg feed. P4 was a group with 10 mL VCO /kg feed. P5 was a group with 5 mL VCO /kg feed.Â Each group repeated five times. Feed and water were given ad libitum for four weeks. The result showed that there was no significant between treatments. Â Keywords : white rat,hepar microanatomy, olive oil, vco